POLA KOMUNIKASI LEMBAGA ASWAJA CENTER DALAM MENSUKSESKAN KEGIATAN PEKAN ASWAJA - Rifqi Maulana Mahri; Yohandi (Fakultas Dakwah Universitas Ibrahimy, 2023)
The Aswaja Center Institute is an institution engaged in handling the cadre activities of students in aswaja material (Ahlusunnah Wal Jama’ah). This institution is under the auspices of the Central Board of IKSASS Santri Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo. In every organization, communication is needed to establish interaction between management or organizational actors. communication that is carried out intentionally in communication creates a certain pattern which is called the pattern of organizational communication. What is the pattern used by the management of the aswaja center in carrying out Aswaja week activities and what is the description of its success? In this paper will be answered. The methodology used in this research is descriptive qualitative. Data collection techniques with observation, interviews and documentation. The theories used include Popi Ruliana’s theory of organizational communication patterns and David C. Korten’s theory of program success. The results of the study stated that the Aswaja Center institution in the success of Aswaja week activities carried out five patterns, including communication patterns for all channels, communication patterns in the form of chains, upward communication patterns, downward communication patterns, and lateral communication patterns. And the success of the Aswaja Center in carrying out each activity can be seen from the suitability indicator between the program and the beneficiaries.